ANALISIS USAHATANI DAN PEMASARAN SALAK PONDOH (Salacca edulis reinw) DI DESA RAMBAH BARU KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Yanda Fauzi Tama; Jumantri '; Cepriadi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the feasibility farming income and marketing of snake fruit pondoh. The research method use is a case study and retrievel technique census respondents with a total population of 29 people snake fruit pondoh farmers and 2 middlemen, 2 small traders. The result showed on average of snake fruit pondoh farming land in the village Rambah Baru 0,31 hectares. Total production cost of snake fruit pondoh farming is Rp.7.868.489/year revenue that the snake fruit pondoh farmers Rp.17.680.000/year and net profit is Rp.9.811.511/year. The Value of Retrun Cost Ratio (RCR) from the analysis of snake fruit pondoh farming is of 2,24. Marginal marketing snake fruit pondoh at Rp.4000/Kg which mean that farming is profitable and possible to continue. Problems faced by farmers snake fruit pondoh include planting and care systems, inadequate institutions and lack of market information so that farmers do not know the target market would be more profitable. So that marketing of snake fruit pondoh which still rely on middlemen or customers who come to the garden. Keyword : anlysis of farm, efficiency, marketing, margin, revenue